Osteomalacia due to Vitamin D Deficiency: A Case Report - Banu Ordahan; Kaan Uslu; Hatice Uğurlu (Galenos Yayinevi, 2020)
Osteomalacia is a metabolic bone disease characterized by demineralization of the newly formed osteoid in adults. Vitamin D deficiency due to insufficient vitamin D intake, inadequate exposure to sunlight, and malabsorption of vitamin D are the most widespread cause of osteomalacia. Here,we present the case of 18 year old female patient who presented to our hospital with complaints of low back pain. Sacral bone pseudofracture was detected by magnetic resonance imaging due to osteomalacia. Patient was treated with vitamin D.